(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
The article provides information about the history of origin, medicinal, economic importance, application and biological properties of Amaranthus L. Conclusions are made based on the results of research on seed germination of amaranth plants in Termez conditions.